Electrospinning and characterization of magnetoelectric NdFeO3–PbZr0.52Ti0.48O3 Core–Shell nanofibers. Issue 13 (1st July 2022) - Yadav, Sandeep Kumar; Hemalatha, J.
Abstract: A core–shell nanofiber with a neodymium orthoferrite (NdFeO3 ) core and lead zirconium titanate (PbZr0.52 Ti0.48 O3 ) shell was prepared in this study using the sol-gel electrospinning method. Structural properties of the nanofiber were analysed using the X-ray diffraction (XRD) method, which revealed that a perovskite structure was formed. The strain was calculated using Williamson-Hall (W–H) plot. Functional groups of the nanofiber were studied using Fourier transform infrared (FTIR) spectroscopy. Morphological studies revealed the core diameter of the nanofiber to be 65 nm and its shell diameter to be 128 nm. The elemental analysis of core-shell nanofiber was made using Energy Dispersive X-ray Spectroscopy (EDS) which proved the formation of NdFeO3 and PbZr0.52 Ti0.48 O3 composite in the stoichiometric ratio. Topography analysis using atomic force microscopy found the average fibre diameter to be 135 nm. The nanofiber exhibited antiferromagnetic behaviour, with a saturation magnetization of 0.48 emu/g. Dynamic contact electrostatic force microscopy (DC-EFM) studies revealed that the nanofiber showed domain-switching behaviour. The ferroelectric hysteresis plots showed that the nanofiber exhibited a maximum polarization of 5.45 μC/cm 2 at 20 kV/cm. Also, its dielectric constant was 268 at 100 Hz. The leakage current study revealed a butterfly-shaped J-E loop, which further proved the ferroelectric behaviour of the nanofiber. The mechanism behind the leakage current was identified to be the Schottky emission. The P-E loops recorded under external magnetic fields of different strengths exhibited variations in the polarization, indicating the presence of cross-coupling between electric and magnetic order parameters. Because of the high dielectric constant displayed by the magnetoelectrically active NdFeO3 –PbZr0.52 Ti0.48 O3 core–shell nanofiber, it can be a promising candidate for a number of applications, such as data storage devices, multimedia devices, spintronics and magnetic field sensors.